Functional Characterization of the Arabidopsis Ammonium Transporter AtAMT1;3 With the Emphasis on Structural Determinants of Substrate Binding and Permeation Properties - Hao, Dong-Li; Yang, Shun-Ying; Liu, Shu-Xia; Zhou, Jin-Yan; Huang, Ya-Nan; Véry, Anne-Aliénor; Sentenac, Hervé; Su, Yan-Hua (Frontiers in Plant Science, 2020)
AtAMT1;3 is a major contributor to high-affinity ammonium uptake in Arabidopsis roots. Using a stable electrophysiological recording strategy, we demonstrate in Xenopus laevis oocytes that AtAMT1;3 functions as a typical high-affinity NH4+ uniporter independent of protons and Ca2+. The findings that AtAMT1;3 transports methylammonium (MeA+, a chemical analog of NH4+) with extremely low affinity (Km in the range of 2.9–6.1 mM) led to investigate the mechanisms underlying substrate binding. Homologous modeling and substrate docking analyses predicted that the deduced substrate binding motif of AtAMT1;3 facilitates the binding of NH4+ ions but loosely accommodates the binding of MeA+ to a more superficial location of the permeation pathway. Amongst point mutations tested based on this analysis, P181A resulted in both significantly increased current amplitudes and substrate binding affinity, whereas F178I led to opposite effects. Thus these 2 residues, which flank W179, a major structural component of the binding site, are also important determinants of AtAMT1;3 transport capacity by being involved in substrate binding. The Q365K mutation neighboring the histidine residue H378, which confines the substrate permeation tunnel, affected only the current amplitudes but not the binding affinities, providing evidence that Q365 mainly controls the substrate diffusion rate within the permeation pathway.